Comparative efficacy and safety of belimumab and hydroxychloroquine in the maintenance phase in patients with systemic lupus erythematosus: a retrospective cohort study - Kimura, Koichi; Ayano, Masahiro; Ota, Shun-Ichiro; Kushimoto, Kazuo; Kimoto, Yasutaka; Mitoma, Hiroki; Ono, Nobuyuki; Arinobu, Yojiro; Akashi, Koichi; Horiuchi, Takahiko; Niiro, Hiroaki (Frontiers in Lupus, 2024)
Objectives: Hydroxychloroquine (HCQ), a cornerstone drug, is recommended for longterm use in treating systemic lupus erythematosus (SLE). However, in cases where HCQ is unavailable, it is unclear which drugs should be prioritised for continuation. We aimed to clarify whether belimumab (BLM), which has recently been reported to have long-term safety and efficacy, could be a viable alternative to HCQ.We retrospectively compared the efficacy, drug continuation rate and safety of HCQ and BLM in the maintenance phase in patients with SLE. The efficacy endpoints were the cumulative incidence of flares over 2 years, the increase in the damage index and the changes in the SLE Disease Activity Index 2000 (SLEDAI) score and prednisolone dose. The safety endpoint was the adverse event rates.Results: Among 96 patients analysed, 15 out of 84 patients (17.9%) in the HCQ group and 1 out of 12 patients (8.3%) in the BLM group experienced a flare with no significant difference in the cumulative incidence of flares between the two groups (p = 0.47). No differences were observed in the cumulative incidence of the increase in the damage index, changes in the SLEDAI score and prednisolone dose, drug continuation rates and adverse events. 4Conclusions: The efficacy and safety of BLM were similar to those of HCQ. BLM could be a valuable treatment option for patients with SLE as an alternative for those who cannot tolerate HCQ.